Dietary Protein Supplementation and Recovery from Femoral Fracture. (29th September 2014) - Porter, Kimberly H.; Johnson, Mary Ann
Abstract : A recent randomized, double-blind, placebo-controlled trial found that protein supplementation improved recovery from femoral fractures in an elderly population. A 6-month course of protein supplementation (20 g/day, 5 days/week) improved serum prealbumin and insulin-like growth factor I (IGF-I) concentrations, minimized bone loss, and decreased length of stay in rehabilitation facilities.